Histology - Heinbockel, Thomas; Shields, Vonnie D.C (IntechOpen, 2019)
Histology is the science of tissues and as such histology studies cells and tissues of organs using a variety of techniques. Histological techniques are used in different disciplines: research, teaching, and clinical applications. This book explores the research currently being carried out at the molecular, subcellular, and cellular levels, both in normal and pathological processes, from genetic mechanisms to intra- and intercellular signaling. This book includes cutting-edge research reviews and descriptions of technological advances to modify bodily cells and tissues. Targeted at students and researchers in biological, medical, and related disciplines, this book will provide an overview of the work being done in this field, and will highlight gaps and areas that would benefit from further exploration. The book contains eight chapters in four sections and presents reviews in different areas of histology written by experts in their respective fields. Basic histology, cell biology, histopathology, and histological techniques are featured prominently as a recurring theme throughout the chapters. This book will be a most valuable resource for histologists, cell biologists, pathologists, and other scientists alike and contribute to the training of current and future biomedical scientists.